(untitled) (Asian Journal of Medical Research and Health Sciences, 2025)
Background: In India, breast cancer presents a significant and growing health burden, characterized by late-stage diagnosis and a lower age of onset compared to Western populations. The gynecologist, as a primary point of contact for women’s health, is uniquely positioned to implement early detection strategies. Objectives: This study aimed to assess the benefits of systematic breast evaluation by gynecologists by determining the prevalence of breast diseases, detecting benign and malignant conditions, and evaluating awareness and practices of breast self-examination [BSE]. Materials and Methods: A cross-sectional study was conducted from October 2022 to November 2024, enrolling 1100 women attending a gynecology outpatient department. Participants were categorized as asymptomatic [n=764] or symptomatic [n=336]. All underwent clinical breast examination [CBE], with subsequent age-appropriate imaging [ultrasonography for ≤40 years; mammography for >40 years]. Suspicious lesions [BIRADS III/IV/V] were investigated by fine-needle aspiration cytology [FNAC]. Results: The prevalence of breast diseases was 15.2%. Overall, 14 women [1.27%] were diagnosed with breast cancer, all in the >40 years age group. The cancer detection rate was 0.7% [5/696] in asymptomatic women over 40 and 5.5% [9/164] in symptomatic women over 40. No malignancies were detected in women aged ≤40 years. Only 10.18% of women practiced BSE regularly, with practice being significantly higher in the symptomatic group [p=0.000]. Significant risk factors associated with symptomatic presentation included nulliparity, late age at first childbirth, and absence of breastfeeding. Conclusion: Integrating systematic breast evaluation into routine gynecological practice is a highly effective strategy for the early detection of breast cancer and benign diseases. It serves as a crucial platform for educating women, thereby potentially reducing late-stage presentation and mortality.